2012
DOI: 10.1176/appi.focus.10.4.452
|View full text |Cite
|
Sign up to set email alerts
|

Developments in Psychopharmacology for Major Depressive Disorder

Abstract: After years of emphasizing the same monoamine-based neurotransmitter mechanisms for treating depression, the antidepressant medication pipeline is broadening its reach. While serotonin, norepinephrine, and dopamine remain important treatment targets, researchers are working on compounds targeting their receptors in novel ways, as well as different combinations of monoaminergic actions that they hope will lead to improved efficacy and/or decreased side effects.At the same time, other researchers are focusing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Multiple studies have supported the efficacy of vilazodone in the treatment of depression [7][8][9]. Given its unique mechanism of action, vilazodone is often called a serotonin partial agonist reuptake inhibitor (SPARI) [4,[10][11][12][13]. Theories of why this medication has shown to be effective include its 5-HT1A partial agonism which, in combination with serotonin transporter (SERT) inhibition, may lead to rapid and robust elevations of synaptic 5-HT.…”
Section: Vilazodonementioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have supported the efficacy of vilazodone in the treatment of depression [7][8][9]. Given its unique mechanism of action, vilazodone is often called a serotonin partial agonist reuptake inhibitor (SPARI) [4,[10][11][12][13]. Theories of why this medication has shown to be effective include its 5-HT1A partial agonism which, in combination with serotonin transporter (SERT) inhibition, may lead to rapid and robust elevations of synaptic 5-HT.…”
Section: Vilazodonementioning
confidence: 99%
“…It can be classified as a triple reuptake inhibitor (TRI) or a serotoninnorepinephrine-dopamine reuptake inhibitor with additional pharmacological properties including 5-HT2C, 5-HT3, 5-HT2A, and alpha-1a antagonism [4,38]. This class of drug holds promise for a robust response by targeting three main neurotransmitters without requiring high occupancy of the serotonin transporter, thus potentially reducing some serotonin mediated side effects [11]. According to a Lundbeck release, in vivo rat studies involving tedatioxetine demonstrated increases in acetylcholine, noradrenaline, dopamine, and serotonin levels in brain regions involved in mood regulation.…”
Section: Tedatioxetinementioning
confidence: 99%